DEVELOPMENT OF LKPD BASED ON ETHNOPEDAGOGY OF SINGOSARI TEMPLE ON CULTURAL LITERACY - Mu'arifah, Mu'arifah; Subrata, Heru; Istiq’faroh, Nurul (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Digital teaching materials are one of the learning tools that can facilitate student learning. The reason for this research is the absence of digital teaching materials and the lack of matching the content of learning materials with the characteristics of students. This study uses a 4D model using only 3 stages due to time constraints, the target of this research is grade VI students of SDN 1 Pagentan Singosari Malang with the type of data used, namely qualitative and quantitative data. The results of the product validity test from the assessment of material experts and linguists obtained an average score of 95.46% which shows very valid criteria. The results of the product attractiveness test from the student and teacher response questionnaire during the limited and field trials obtained an average score of 86.71% and 93.29% which shows very interesting criteria. The results of the product practicality test were obtained from the teacher's response questionnaire (94.82%) and the student's response (84.61%) which showed very practical criteria. . Eth-nopedagogy-based LKPD products also show effective criteria for an increase in student learning activities and teacher activities before and during the use of LKPD, namely the previous student activity from 46.75% to 82.24% while the previous teacher's activity was 74.43% to 90.27% so that it can be concluded that ethnopedagogy-based LKPD is very effective in increasing student and teacher activities in learning. Based on these results, ethnopedagogy-based LKPD for use in elemen-tary schools has met the requirements for use in learning because it has met the criteria of validity, attractiveness, effectiveness, and practicality.